2016
DOI: 10.1007/s00127-016-1230-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antenatal depression and associated factors among pregnant women hospitalized in a high-risk pregnancy unit in Greece

Abstract: Approximately one quarter of pregnant women hospitalized in the HRPU may show signs of depression at the time of admission. Smoking and an unwanted pregnancy were found to be independently associated with antenatal depression, whereas no association was found with any obstetric parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
4
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 40 publications
5
37
4
6
Order By: Relevance
“…A medically high‐risk pregnancy is defined as “any pregnancy in which there is evidence of actual or potential threat of harm to the life or health of the mother and/or the baby, because of a disorder or situation coincidental with or unique to pregnancy.” Health conditions that lead to increased risk can be obstetrical (eg, placenta previa), maternal (eg, preeclampsia), and/or fetal (eg, prematurity) . Approximately 15%‐20% of pregnancies are affected by these complications each year with a prevalence of complicated pregnancies of 20% estimated in both Canada and the United States for 2016 . Medical complications impact not only the health and well‐being of the mother but also her developing infant (and the entire family).…”
Section: Introductionmentioning
confidence: 99%
“…A medically high‐risk pregnancy is defined as “any pregnancy in which there is evidence of actual or potential threat of harm to the life or health of the mother and/or the baby, because of a disorder or situation coincidental with or unique to pregnancy.” Health conditions that lead to increased risk can be obstetrical (eg, placenta previa), maternal (eg, preeclampsia), and/or fetal (eg, prematurity) . Approximately 15%‐20% of pregnancies are affected by these complications each year with a prevalence of complicated pregnancies of 20% estimated in both Canada and the United States for 2016 . Medical complications impact not only the health and well‐being of the mother but also her developing infant (and the entire family).…”
Section: Introductionmentioning
confidence: 99%
“…Also, a research which was completed in Hyderabad showed 18% prevalence of depression. Mumford et al found a high prevalence (46%) of depression and anxiety among women in neighboring Chitral, Pakistan, where he used Bradford Somatic Inventory [8].…”
Section: Discussionmentioning
confidence: 99%
“…A baixa escolaridade materna ou a ausência de educação formal e o desemprego, tanto da própria gestante como do cônjuge ou de outro membro familiar, foram identificados como fatores de risco para a depressão na gravidez em quatro estudos cada (19,25,31,36,37,43,(48)(49) .…”
Section: /Etiópiaunclassified
“…Quatro estudos identificaram a presença de doenças ou sintomas relacionados à saúde física como fator de risco para a ocorrência da depressão no período gestacional (23,28,35,39) . (25,27,35,37,45,(48)(49)51) .…”
Section: /Etiópiaunclassified